Corporate presence in healthcare sector in India - Indira Chakravarthi (Social Medicine, 2011)
Various forms of privatization have been the preferred policy option for the health sector reform which was initiated in the 1990s in India under the neo-liberal regime. Rigorous study of privatization processes and of the private sector in general remains inadequate. This research attempts to fill this gap by examining the extent and nature of corporate presence in India in the delivery of healthcare services. It poses some concerns in light of experiences of other countries. The first section of the paper covers the private hospitals sector. The second part looks at the diagnostics sector. The concluding section discusses the implications of such developments for healthcare services in the country.